The Variation Tendency of Polyamines Forms and Components of Polyamine Metabolism in Zoysiagrass (Zoysia japonica Steud.) to Salt Stress with Exogenous Spermidine Application - Li, Shucheng; Cui, Linlin; Zhang, Yujuan; Wang, Yunwen; Mao, Peisheng (Frontiers in Physiology, 2017)
To understand dynamic changes in polyamines (PAs) forms and components of polyamine metabolism in zoysiagrass (Zoysia japonica Steud.) response to salt stress with exogenous spermidine (Spd) application, two Chinese zoysia cultivars, z081 and z057, were exposed to sodium chloride stress for 2, 4, 6, and 8 days. The z057 cultivar possesses higher salinity tolerance than the z081 cultivar. Salt stress decreased the zoysiagrass fresh weight and increased free Spd and spermine (Spm) levels and soluble and insoluble putrescine (Put), Spd and Spm levels in both cultivars. Moreover, salt stress enhanced the activities of arginine decarboxylase (ADC), ornithine decarboxylase (ODC), S-adenosylmethionine decarboxylase (SAMDC) and diamine oxidase (DAO). Exogenous Spd increased PA metabolism and ADC, SAMDC and DAO activities and decreased free Put levels under salt stress conditions in both cultivars. In addition, structural equation modeling (SEM) showed that ODC, SAMDC and DAO contributed to PA metabolism, and endogenous Spd levels also contributed to endogenous Spm levels. Free PAs may be the primary factor influencing the variation of other PA forms. SEM also indicated that ADC and polyamine oxidase (PAO) play a limited role in enhancing zoysia salt tolerance via PA metabolism under salt stress.